A Web-Based Adolescent Positive Psychology Program in Schools: Randomized Controlled Trial - Burckhardt, Rowan; Manicavasagar, Vijaya; Batterham, Philip J; Miller, Leonie M; Talbot, Elizabeth; Lum, Alistair (JMIR Publications, 2015)
BackgroundAdolescent mental health is characterized by relatively high rates of psychiatric disorders and low levels of help-seeking behaviors. Existing mental health programs aimed at addressing these issues in adolescents have repeated inconsistent results. Such programs have generally been based on techniques derived from cognitive behavioral therapy, which may not be ideally suited to early intervention among adolescent samples. Positive psychology, which seeks to improve well-being rather than alleviate psychological symptoms, offers an alternative approach. A previous community study of adolescents found that informal engagement in an online positive psychology program for up to 6 weeks yielded significant improvements in both well-being and depression symptoms. However, this approach had not been trialed among adolescents in a structured format and within a school setting. ObjectiveThis study examines the feasibility of an online school-based positive psychology program delivered in a structured format over a 6-week period utilizing a workbook to guide students through website content and interactive exercises. MethodsStudents from four high schools were randomly allocated by classroom to either the positive psychology condition, "Bite Back", or the control condition. The Bite Back condition consisted of positive psychology exercises and information, while the control condition used a series of non-psychology entertainment websites. Both interventions were delivered online for 6 hours over a period of 4-6 weeks during class time. Symptom measures and measures of well-being/flourishing and life satisfaction were administered at baseline and post intervention. ResultsData were analyzed using multilevel linear modeling. Both conditions demonstrated reductions in depression, stress, and total symptom scores without any significant differences between the two conditions. Both the Bite Back and control conditions also demonstrated significant improvements in life satisfaction scores post intervention. However, only the control condition demonstrated significant increases in flourishing scores post intervention. ConclusionsResults suggest that a structured online positive psychology program administered within the school curriculum was not effective when compared to the control condition. The limitations of online program delivery in school settings including logistic considerations are also relevant to the contradictory findings of this study. Trial RegistrationAustralian New Zealand Clinical Trials Registry: ACTRN1261200057831; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=362489 (Archived by Webcite at http://www.webcitation.org/6NXmjwfAy).